Third PAllas Cloud Experiment (PACE III): Campaign Description - Hyvärinen, A-P.; Komppula, M.; Miettinen, P.; Spiegel, J.K.; Noziére, B.; Ekström, S.; Neitola, K.; Brus, D. (David); Asmi, E.; Kivekäs, N.; Leskinen, A.; Portin, H. (2010)
The Third PAllas Cloud Experiment, PACEIII, took place from 11th of September to 10th of October 2009. Studies of the size-dependent activation efficiencies and the role of chemistry and environmental factors on cloud droplet activation and cloud properties were made using a multidisciplinary approach.